Injectable DaxibotulinumtoxinA for the Treatment of Glabellar Lines: A Phase 2, Randomized, Dose-Ranging, Double-Blind, Multicenter Comparison With OnabotulinumtoxinA and Placebo. Issue 11 (November 2017) - Carruthers, Jean; Solish, Nowell; Humphrey, Shannon; Rosen, Nathan; Muhn, Channy; Bertucci, Vince; Swift, Arthur; Metelitsa, Andrei; Rubio, Roman G.; Waugh, Jacob; Quiring, John; Shears, Gill; et al.
Abstract : BACKGROUND: Injectable daxibotulinumtoxinA (RT002) is an investigational botulinum toxin Type A in clinical development. It is formulated with a proprietary peptide and offers the potential of a longer acting neurotoxin therapy. OBJECTIVE: To compare the safety, efficacy, and duration of response of daxibotulinumtoxinA with onabotulinumtoxinA and placebo [www.clinicaltrials.gov NCT02303002]. METHODS: In this Phase 2, randomized, dose-ranging, parallel-group, double-blind, multicenter study, subjects with moderate or severe glabellar lines at maximum frown were randomly assigned to 20U, 40U, or 60U daxibotulinumtoxinA, 20U onabotulinumtoxinA, or placebo. Glabellar line severity was evaluated by investigators and subjects at least every 4 weeks, for at least 24 weeks. RESULTS: Overall, 268 subjects enrolled. Statistical and clinical superiority were observed for 40U and 60U daxibotulinumtoxinA over 20U onabotulinumtoxinA for a range of efficacy outcomes despite the study not being powered to detect statistically significant differences between these active treatment groups. CONCLUSION: The 40U dose of daxibotulinumtoxinA was well tolerated (e.g., absence of ptosis) and had the most favorable risk: benefit profile. Compared with 20U onabotulinumtoxinA, it exhibited a significantly greater response rate and a significantly longer duration of response (median of 24 weeks vs 19 weeks; p = .030).